Facile Synthesis of Substituted Trifluoromethyl Piperidines with Diversifying Functionalization - Jatoi, Wahid B.; Balouch, Ashique Hussain; Khaskheli, Mazhar Iqbal; Shahani, Nafeesa Khatoon; Shaikh, Qurat-Ul-Ain; Katohar, Nisar Ahmed (Letters in Organic Chemistry, 2021)
Piperidine-based alkaloids are undoubtedly an important class of biologically active natural products. When a unique group, like trifluoromethyl (Tfm), is added to an active compound, it significantly ameliorates its bioactivity, bioavailability, physical, and chemical properties. Many fluorination and trifluoromethylation methods have been reported. In the present paper, we have shown that among all other trifluoromethylation pathways, the Mannich reaction has the great tendency to introduce the Tfm group in a saturated or aromatic heterocyclic compound. Applications of this reaction are elaborated in preparing several derivatives of piperidine-based alkaloids with trifluoromethyl at α-position. Furthermore, the substitution at C-4 and C-6 was successfully achieved with a variety of saturated and aromatic groups.
Keywords: piperidines